2022
DOI: 10.1101/2022.08.05.22278462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnic inequalities in age-related patterns of multiple long-term conditions in England: analysis of primary care and nationally representative survey data

Abstract: Background Having multiple long-term conditions has been associated with a higher treatment burden, reduced quality of life and a higher risk of mortality. Epidemiological evidence suggests that people from minoritised ethnic groups have a higher prevalence of multiple long-term conditions (MLTCs) but questions remain regarding the patterning of MLTCs by age, how this varies for different ethnic group populations, and across conceptualisations of MLTCs (for example, MLTCs with and without mental health conditi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…General multimorbidity varied with age among ethnic groups, with the risk being greater among the British White population aged under 40, and greater among ethnic minorities (Pakistani and Bangladeshi) aged 40 and over. Age-related differences in patterns of multimorbidity by ethnicity, was also found in a recent study,(22). This correlates well with the increased risk of cardiovascular multimorbidity among Pakistani and Bangladeshi adults aged 40 and over; however, differences between other ethnic groups and greater risk of cardiovascular multimorbidity but not general multimorbidity suggest the general white population has higher prevalence of non-cardiovascular longstanding conditions and/or there are ethnic differences in reporting or in being diagnosed.…”
Section: Discussionsupporting
confidence: 79%
“…General multimorbidity varied with age among ethnic groups, with the risk being greater among the British White population aged under 40, and greater among ethnic minorities (Pakistani and Bangladeshi) aged 40 and over. Age-related differences in patterns of multimorbidity by ethnicity, was also found in a recent study,(22). This correlates well with the increased risk of cardiovascular multimorbidity among Pakistani and Bangladeshi adults aged 40 and over; however, differences between other ethnic groups and greater risk of cardiovascular multimorbidity but not general multimorbidity suggest the general white population has higher prevalence of non-cardiovascular longstanding conditions and/or there are ethnic differences in reporting or in being diagnosed.…”
Section: Discussionsupporting
confidence: 79%
“…Two recent studies based on CPRD show that compared with other ethnic groups, people of Chinese ethnicity have the lowest mean number of EHR-determined long-term conditions and lowest prevalence of complex multimorbidity across all age groups. 33 , 34 Our study suggests the predictive value of diagnosed and self-reported conditions within the Chinese ethnicity is lower than others ethnic groups. A possible explanation to this might be lower diagnoses of medical conditions in this subpopulation.…”
Section: Discussionmentioning
confidence: 63%
“…Similar age-related differences in patterns of multimorbidity by ethnicity were also found in a recent study, where a lower prevalence of multiple long-term conditions was found among younger ethnic groups compared with the White majority, based on data from primary care records. 22 A greater risk of cardiovascular multimorbidity, but not general multimorbidity, among ethnic groups suggests a higher prevalence of non-cardiovascular longstanding conditions among the White population and/or variations in reporting or in being diagnosed among ethnic groups. Chinese and Asian Indian adults were less likely to report having multimorbidity in the USA according to a study by Zhang et al; however, they were more likely to have a combination of high cholesterol and hypertension, risk factors for CVD consistent with our study.…”
Section: Discussionmentioning
confidence: 99%